Studies on Ranunculus Population: Isozymic Pattern - SURANTO SURANTO (Biodiversitas Journal of Biological Diversity, 2001)
Species of Ranunculus is small herb grows at quite high altitudes, ranging from several hundreds to more than a thousand meter above sea level. They can occupy a variety of habitats such as moist soils or can even grow sub merged or floating in stream. A few numbers of species from different populations have been recorded to have morphological complexity, which could cause a problem for the work of taxonomists in making decisions. In order to support taxonomists in solving their problem, a new experimental method using SDS-PAGE will be used to explore the isozyme data. The main purpose of this research was to investigate whether or not isozyme data can be used to clarify the morphological complexity of Ranunculus species. In this study, nine species of Ranunculus from different populations were used. Five to twenty plants were sampled for electrophoresis studies. Four enzyme systems: peroxidase, esterase, malate dehydrogenase and acid phosphatase were chosen. The results showed that every enzyme gave its specific pattern in each species and common band always found in nine species tested. This experiment proved that genetic data (isozyme) quite promoting to be applied in higher plant taxonomy in solving themorphological complexity problem.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey words: isozyme, PER, EST, MDH, ACP, Ranunculus